Physiologic anisocoria under various lighting conditions - Steck RP (Dove Medical Press, 2018)
Ryan P Steck,1 Min Kong,2 Kaydee L McCray,3 Valerie Quan,3 Pinakin Gunvant Davey3 1Western University of Health Sciences, College of Osteopathic Medicine of the Pacific, Pomona, CA, USA; 2Visual Science and Optometry Center, The People’s Hospital of Guangxi Nanning, Zhuang Autonomous Region, China; 3Western University of Health Sciences, College of Optometry, Pomona, CA, USA Purpose: To evaluate the measurement of anisocoria in a group of ocular healthy subjects using a standardized protocol in scotopic, mesopic, and photopic lighting conditions, and determine the optimal threshold of difference in pupil diameter in determining physiologic anisocoria.Methods: Right and left pupil diameters of 126 ocular healthy subjects with a mean age 30.5±7.8 years (40 males and 86 females) were measured sequentially under photopic conditions using a monocular infrared pupillometer. A sub-group of 51 individuals had right and left pupil measurements performed under three additional lighting conditions, allowing for a 2-minute recovery between measurements. A white light emitting diode (LED) in the eyecup of the pupillometer produced three controlled light settings: scotopic (0 lux), low mesopic (0.3 lux), and high mesopic (3 lux). The criterion for anisocoria was defined as ≥0.4 mm difference in pupil diameter between the eyes.Results: In the 126 subjects tested, 23.8% (n=30) exhibited anisocoria in photopic conditions. In the sub-group measured under three additional light settings, 43.1% (n=22) exhibited anisocoria in scotopic conditions, 43.1% (n=22) in low mesopic conditions, and 47.1% (n=24) in high mesopic conditions. Approximately 73% of subjects exhibited anisocoria in at least one light setting, while only approximately 8% had anisocoria in every light setting. When the criterion for anisocoria was shifted to ≥0.2 mm or ≥0.6 mm, the prevalence of anisocoria shifted significantly. Using a higher cutoff of ≥0.6 mm effectively reduced the number of healthy individuals who exhibit anisocoria in every light setting to almost zero.Conclusion: Based on our data, anisocoria is more prevalent under varied lighting conditions. To ensure the anisocoria is due to physiologic reasons, one should ensure that it is present under all lighting conditions to avoid excessive false positives. Keywords: anisocoria, pupillometry, pupil diameter